Nitric Oxide and Electrophilic Cyclopentenone Prostaglandins in Redox signaling, Regulation of Cytoskeleton Dynamics and Intercellular Communication - Bago, Ángel; Íñiguez, Miguel A.; Serrador, Juan M. (Frontiers in Cell and Developmental Biology, 2021)
Nitric oxide (NO) and electrophilic cyclopentenone prostaglandins (CyPG) are local mediators that modulate cellular response to oxidative stress in different pathophysiological processes. In particular, there is increasing evidence about their functional role during inflammation and immune responses. Although the mechanistic details about their relationship and functional interactions are still far from resolved, NO and CyPG share the ability to promote redox-based post-translational modification (PTM) of proteins that play key roles in cellular homeostasis, signal transduction and transcription. NO-induced S-nitrosylation and S-glutathionylation as well as cyclopentenone-mediated adduct formation, are a few of the main PTM by which intra- and inter-cellular signalling are regulated. There is a growing body of evidence indicating that actin and actin-binding proteins are susceptible to covalent PTM by these agents. It is well known that the actin cytoskeleton is key for the establishment of interactions among leukocytes, endothelial and muscle cells, enabling cellular activation and migration. In this review we analyse the current knowledge about the actions exerted by NO and CyPG electrophilic lipids on the regulation of actin dynamics and cytoskeleton organization, and discuss some open questions regarding their functional relevance in the regulation of intercellular communication.